Effect of B, Zr, and C on Hot Tearing of a Directionally Solidified Nickel-Based Superalloy - Grodzki, Jacek; Hartmann, Nadine; Rettig, Ralf; Affeldt, Ernst; Singer, Robert (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2016)
The effect of the minor elements B, Zr, and C on the castability of a Nickel-based γ′-strengthened superalloy has been investigated. Tube-like specimens were prepared by directional solidification where the rigid ceramic core leads to hoop stresses and grain boundary cracking. It was found that an important improvement in castability can be achieved by adjusting the minor elemental composition. Too low C (≤0.15 pct) and too high B and Zr contents (≥0.05 pct) lead to material that is very prone to solidification cracking and should be avoided. The results cannot be rationalized on the basis of the current models for solidification cracking. Instead, pronounced hot tearing is observed to occur at high amounts of γ/γ′-eutectic and high Zr contents. The critical film stage where dendrites at the end of solidification do not touch and are separated by thin liquid films must be avoided. How Zr promotes the film stage will be discussed in the paper.